Between Soundscape Studies and semiotics: from the sound effect to the sense effects of the sound environment - Battistini, Emiliano (E|C, 2020)
This paper summarises the lecture notes developed for the workshop “Analysis of the sonic space” carried out at Bologna University in October 2016, as part of the class “Methodology 2” held by professor Patrizia Violi. The workshop dealt with the semiotics of soundscape and involved the students of the Master in Semiotics (Department of Philosophy and Communication, Bologna University, academic year 2016/2017) through frontal lectures, field analysis experiences, collective presentations and a final discussion. After discussing the current interest on five senses and multi-sensorial perspective in Humanities related to the crisis of the concept of landscape, our work introduces the sonic semiotics in relation to the space, starting with the sonic concepts developed during the XX century: sonic object, soundscape and sonic effect. The sonic semiotics doesn’t study “sonic effects” but concerns “sonic effects of meaning”: we propose to start from the concept of soundscape to develop a “semiotic of the audible” useful to study every sonic phenomena. A series of semiotic models useful for the analysis of sound are presented, focusing on the problem of how consider figurative and plastic formants in sonic textualities. Finally, the paper introduces the workshop experience and the methodological recommendations to proceed with the analysis of the soundscape of three public places of Bologna – the “Stazione Centrale” (the central railway station), the “Mercato delle Erbe” (an historical covered market) and “Salaborsa” (the biggest public library) – taken as case studies by our students.